Efficacy of a Gel Containing Polihexanide and Betaine in Deep Partial and Full Thickness Burns Requiring Split-thickness Skin Grafts: A Noncomparative Clinical Study - Kiefer, Jurij; Harati, Kamran; Müller-Seubert, Wibke; Fischer, Sebastian; Ziegler, Benjamin; Behr, Bjoern; Gille, Jochen; Kneser, Ulrich; Lehnhardt, Marcus; Daigeler, Adrien; Dragu, Adrian (Journal of Burn Care & Research, 2018)
Despite overall advances in burn therapy, wound infection remains one of the leading causes of morbidity and mortality in patients with severe burn injuries. This prospective, multicenter, noncomparative clinical trial was conducted to assess the efficacy and safety of Prontosan® Wound Gel X (PWX), a gel containing polihexanide and betaine, for moistening and cleansing in deep tissue burn wounds requiring split-thickness skin grafting. Patients with deep partial or full thickness burn wounds requiring split-thickness skin grafting were treated with the gel to evaluate its tolerability and safety as well as graft take and the healing of the skin graft. Target wounds were assessed clinically and by using a photo-planimetric analyzing software for re-epithelialization. From 04/2012 to 05/2015, burn patients from three burn centers in Germany were screened for the study, of which 51 patients met the inclusion criteria. Predominantly deep partial thickness burn wounds were found (88.2 %). Except for one graft failure, all patients reached complete re-epithelialization after one (n = 14), two (n = 31), or three (n = 5) administrations of the gel. The median time to complete graft take was 7 days and was below the average healing time reported in comparable studies. No wound infection or erythema occurred. This is the first study to document the outcomes of deep partial and full thickness burns treated with PWX for moistening and cleansing. The gel was shown to be efficacious, safe, and well tolerated for use in burn wounds requiring split-thickness skin grafts.
EVALuna2:50999